The teaching of afro-Brazilian history and culture through samba: O ensino da história e cultura afro-brasileira através do samba (Revista de História da UEG (REVHIST), 2022)
This article is a theoretical and methodological study that aims to contribute to the use of samba in the teaching of history in basic education, mainly the teaching of Afro-Brazilian history and culture. This musical genre, created by the Afro-descendant population in the first decades of the twentieth century, is an essential historical source to know their lives, history and culture in Brazil over time. Thus, it is also configured as a didactic and pedagogical resource to teach Brazilian history as understood from below, and to teach various historical processes from the perspective of the oppressed classes. Our methodology consists on a theoretical debate on the relations between history, its teaching and music, followed by methodological proposals and analysis of three compositions with possible didactic activities. In our perspective, bringing samba to the classroom is one of the ways to build an anti-racist education, based on democratic and egalitarian values.Keywords: History. Afro-Brazilian history and culture. History teaching. Samba.